Millet (Eleusine coracana) Flour Fortification in Composite Bread - Subedi, Ishwar; Harnisch, Christina; Kater, Gerhard; Adhikari, Tulashi (Journal of Food Science and Technology Nepal, 2014)
Composite bread prepared by wheat our (550 types, moisture 10.85%) and millet (Eleusine coracana) flour (moisture 10.8%) were determined to evaluate bread qualities by 2 methods. The first method included application of raw millet flour, where as the second methods included cooked (gelatinized) millet flour before baking. The breads were named as (0MB) only from wheat flour followed by (10CCMB), (20CCMB) and (30CCMB) using 10, 20 and 30 % coarse (669µm) cooked millet flour respectively where as (10FCMB) and (10FUMB) were named as fine (431µm) sized millet flour. The former was gelatinized where as the later wasn’t. These composite breads were made from a blend of 90, 80 and 70 parts of wheat flour with 10, 20 and 30 parts of millet flour respectively. The bread with 10, 20 and 30% composite flour were similar in crumb porosity, texture, smell and taste where as 30% millet flour had higher dough and bread yield. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10614 J. Food Sci. Technol. Nepal, Vol. 7 (86-89), 2012